Clinical Diversity in Focal Congenital Hyperinsulinism in Infancy Correlates With Histological Heterogeneity of Islet Cell Lesions - Craigie, Ross J.; Salomon-Estebanez, Maria; Yau, Daphne; Han, Bing; Mal, Walaa; Newbould, Melanie; Cheesman, Edmund; Bitetti, Stefania; Mohamed, Zainab; Sajjan, Rakesh; Padidela, Raja; Skae, Mars; et al. (Frontiers in Endocrinology, 2018)
BACKGROUND: Congenital Hyperinsulinism (CHI) is an important cause of severe and persistent hypoglycaemia in infancy and childhood. The focal form (CHI-F) of CHI can be potentially cured by pancreatic lesionectomy. While diagnostic characteristics of CHI-F pancreatic histopathology are well recognised, correlation with clinical phenotype has not been established. AIMS: We aimed to correlate the diversity in clinical profiles of patients with islet cell organisation in CHI-F pancreatic tissue. METHODS: Clinical datasets were obtained from twenty-five patients with CHI-F due to ABCC8/KCNJ11 mutations. 18F-DOPA PET-CT was used to localize focal lesions prior to surgery. Immunohistochemistry was used to support protein expression studies. RESULTS: In 28% (n=7) of patient tissues focal lesions were amorphous and projected into adjoining normal pancreatic tissue without clear delineation from normal tissue with CHI-F. In these cases, severe hypoglycaemia was detected within, on average, 2.8 ± 0.8 (range 1-7) days following birth. By contrast, in 72% (n=18) of tissues focal lesions were encapsulated within a defined matrix capsule. In this group, the onset of severe hypoglycaemia was generally delayed; on average 46.6 ± 14.32 (range 1-180) days following birth. For patients with encapsulated lesions and later-onset hypoglycaemia, we found that surgical procedures were curative and less complex. CONCLUSION. CHI-F is associated with heterogeneity in the organisation of focal lesions, which correlates well with clinical presentation and surgical outcomes.